(untitled) (Ágora de Heterodoxias, 2021)
The pedagogy of love, joy and play is theoretically constructed as an integrative statement-category with pedagogical, psychological and ethical-political notions, which implies thinking of education as a space for strengthening humanizing processes that tend to form values, based on which are potentiated to generate transforming systemic effects. This statement has important repercussions on pedagogical practices, making the school a space for the recognition of subjects, valuing not only the cognitive, but also the affective and existential. The methodology is based on a qualitative approach, of the analytical and documental type, on traits exposed by pedagogues that point to the notion of the pedagogy of love, also including references of joy and play. In conclusion, actions are projected and consider that teachers must implement to ensure the learning processes in articulation with educational communities. Also considers the consequences that may have in the transition from a traditional pedagogy to one that seeks the integral development of the human being and belonging to a society in constant evolution, contributing to the formation of their own personality with affective principles, from which happiness, love and play become a fundamental part of their lifelong learning.